H.C. Andersen and Bulgaria: The apolitical writer and traveller meeting communities at a Bazaar - Mihaylova, Nadezhda (Aktualitet - Litteratur, kultur og medier, 2019)
The humanistic values in H.C. Andersen’s works have made an impact on Bulgarian culture. The paper outlines the two-way intercultural relationship of H.C. Andersen’s works and Bulgaria – the first part focuses on his description of this country in A Poet’s Bazaar (1846) and the second on the reception of his works in Bulgarian culture. In his travelogue Andersen shared his impressions of Bulgaria and showed compassion to its people, proving to be a real cosmopolitan and taking a non-political but humanistic attitude to the rebellious events on the Balkans in 1841, influencing the way his Danish and European readers look upon this part of the world. The other aspect of the intercultural relationship focuses on the reception of H.C. Andersen’s works in Bulgaria. It outlines the three main phases in this process, discussing the translations made from different languages and their editions. These publications have an impact on the Bulgarian language, the formation of expressions and set phrases. They prove to be another means of inter-cultural exchange, overcoming the limitations of regional belonging and national identity, while transferring universal values. H.C. Andersen’s ideas of cosmopolitanism and universalism help us adapt ourselves to the constantly changing communities we live in.